2015
DOI: 10.3389/fpsyg.2015.01333
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of math anxiety – an overview and implications

Abstract: Math anxiety is a common phenomenon which can have a negative impact on numerical and arithmetic performance. However, so far little is known about the underlying neurocognitive mechanisms. This mini review provides an overview of studies investigating the neural correlates of math anxiety which provide several hints regarding its influence on math performance: while behavioral studies mostly observe an influence of math anxiety on difficult math tasks, neurophysiological studies show that processing efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…According to these approaches, children with higher levels of anxiety would display more worrying thoughts which, in turn, would detract some of the WM resources necessary to successfully perform the tasks. Consequently, performance might be negatively affected and anxious individuals would end up needing to increase their cognitive effort in order to compensate for their fewer resources (Artemenko et al ., ). Paradoxically, these students might not be willing to put in the extra effort required under certain circumstances (Ashcraft & Moore, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to these approaches, children with higher levels of anxiety would display more worrying thoughts which, in turn, would detract some of the WM resources necessary to successfully perform the tasks. Consequently, performance might be negatively affected and anxious individuals would end up needing to increase their cognitive effort in order to compensate for their fewer resources (Artemenko et al ., ). Paradoxically, these students might not be willing to put in the extra effort required under certain circumstances (Ashcraft & Moore, ).…”
Section: Discussionmentioning
confidence: 97%
“…Two measures of anxiety were used: trait and math anxiety. It can be assumed that they are different yet related constructs (Artemenko, Daroczy, & Nuerk, ). The meta‐analysis performed by Hembree () showed that the mean correlation between both types of anxiety was .35.…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence comes also from physiological (e.g. Ashcraft, 2002) and neuroscientific studies (Artemenko, Daroczy, & Nuerk, 2015 for discussion and some controversies), which can typically dissociate math and general anxiety.…”
Section: Math Anxiety -A Specific Instance Of Anxietymentioning
confidence: 99%
“…Converging evidence comes also from physiological (e.g. Ashcraft, 2002) and neuroscientific studies (Artemenko, Daroczy, & Nuerk, 2015 for discussion and some controversies), which can typically dissociate math and general anxiety.However, MA cannot be subsumed under poor math skills either. It negatively correlates with math achievement, although only moderately (averaged correlation -.27; Ma, 1999 for meta-analysis).…”
mentioning
confidence: 99%
“…MA has been defined by Richardson and Suinn as "a feeling of tension and anxiety that interferes with the manipulation of numbers and the solving of mathematical problems in a wide variety of ordinary life and academic situations" (Richardson & Suinn, 1972, p. 551). MA correlates with performance, academic achievement, avoidance behavior in maths-related situations and even life-choices such as education subjects and career destinations (for review see Artemenko, Daroczy & Nuerk, 2015;Suárez-Pellicioni, Núñez-Peña, & Colomé, 2016).…”
Section: Introductionmentioning
confidence: 99%